2013
DOI: 10.1111/eci.12118
|View full text |Cite
|
Sign up to set email alerts
|

Targeting inflammatory pathways in myocardial infarction

Abstract: Acute cardiomyocyte necrosis in the infarcted heart generates Damage-Associated Molecular Patterns (DAMPs), activating complement and Toll-Like Receptor (TLR)/Interleukin (IL)-1 signaling, and triggering an intense inflammatory reaction. Infiltrating leukocytes clear the infarct from dead cells, while activating reparative pathways that lead to formation of a scar. As the infarct heals the ventricle remodels; the geometric, functional and molecular alterations associated with post-infarction remodeling are dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 71 publications
1
130
0
3
Order By: Relevance
“…17,18,19 Here, we used several complementary animal models, as well as patients' samples, to demonstrate the role of TREM-1 in orchestrating the inflammatory response triggered by MI. Genetic invalidation or pharmacological blockade of Trem-1 inhibits the recruitment of inflammatory cells to the infarcted myocardium and their activation.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,19 Here, we used several complementary animal models, as well as patients' samples, to demonstrate the role of TREM-1 in orchestrating the inflammatory response triggered by MI. Genetic invalidation or pharmacological blockade of Trem-1 inhibits the recruitment of inflammatory cells to the infarcted myocardium and their activation.…”
Section: Discussionmentioning
confidence: 99%
“…These concepts suggested that subsets of leucocytes could infiltrate cardiomyocytes exerting cytotoxic effects so that ischaemic injury extended [14]. Experimental studies targeting leucocytemediated inflammation in myocardial ischaemia and reperfusion showed a marked reduction in infarct size and prevented the extension of ischaemic cardiomyocyte injury [15][16][17][18].…”
Section: Classical Pathophysiological View Of Myocardial Injury and Rmentioning
confidence: 99%
“…LFA-1 is critical in this step, given that its inhibition blocks transmigration and reduces neutrophil extravasation [38,39]. Both antibody neutralization studies [16] and genetic models [40] show the huge importance of b2-integrins for the recruitment of neutrophils in the infarcted heart [18].…”
Section: Neutrophilsmentioning
confidence: 99%
“…The infusion catheter was placed immediately distal to the previously deployed stent. Coronary angiography was repeated 3 minutes after IK-5001 implantation, and biomarkers (including creatine kinase and creatine kinase, muscle and brain) were obtained at 8,16, and 24 hours after device deployment.…”
Section: Study Procedures and Device Deploymentmentioning
confidence: 99%